Multiple ossified spinal meningiomas in the thoracic spine: A case report and literature review - Dong, Chunke; Liu, Yi; Zhu, Yuting; Wei, Hongyu; Ma, Yuzhuo (Frontiers in Surgery, 2022)
Background Ossified spinal meningioma (OSM) is a rare form of a spinal tumor. The surgical strategies and pathologic findings related to OSM have been investigated in recent years. However, multiple OSMs are rarely reported. Here, we intend to present a rare case of multiple OSMs and review the relevant published literature. Case Presentation A 76-year-old woman experienced a progressive sensorimotor disturbance in her bilateral lower limbs for the past 2 years. She complained of inability to walk, urinary incontinence, and chronic constipation when referred to our hospital. A neurological examination revealed a diminished sensation below the bilateral T7, and her neurological status was Nurick Grade 6. Magnetic resonance imaging (MRI) revealed multiple intradural-extramedullary neoplasms at the T7–T11 level. Computed tomography (CT) scans showed five high-density masses of varying sizes in the spinal canal at the T7–T12 level. The patient underwent tumor resection through T7–T11 laminectomy. A histopathological examination revealed multiple OSMs. Conclusion We reported a rare case of multiple OSMs in an elderly patient. After one-stage complete resection, the patient recovered with satisfactory curative effect. Although elderly patients will face various postoperative complications due to their poor physical condition, we still recommend one-stage complete resection of multiple OSMs to reduce recurrence.